Mapping the Intellectual Landscape of Inclusive Islamic Religious Education: A Bibliometric Analysis - Inayati, Nurul Latifatul; Al Mubarok, Fahmi Ulum; Rohmani, Annas Fajar; Yuzarni, Silvani; Musyaffa, Zaim Hilmi (Jurnal Pendidikan Islam, 2025)
Purpose – This study aims to systematically map the scholarly landscape of inclusive Islamic education, particularly Islamic Religious Education (PAI) for children with special needs (CWSN), by identifying trends, key themes, influential authors, and patterns of collaboration in the literature. Design/methods/approach – A bibliometric analysis was conducted on 154 Scopus-indexed journal articles published between 2003 and 2025. The data were extracted on July 19, 2025, at 8:50 p.m., using a refined Boolean search strategy. The corpus was limited to Scopus-indexed journal articles published in English, and only journal articles were included based on the document filter. The extracted data were analyzed using R, RStudio, VOSviewer, and Microsoft Excel to assess publication metrics, co-authorship networks, and keyword evolution. Findings – The results show a significant increase in research output after 2019, with Southeast Asian countries—particularly Indonesia and Malaysia—leading in contributions. Dominant themes include inclusive education, Islamic pedagogy, and children with special needs, while emerging themes such as pluralism, citizenship, and social justice reflect a shift toward more justice-oriented and contextually grounded discourse. However, international collaboration remains limited, and the theoretical integration between Islamic epistemology and inclusive education principles appears underdeveloped. Research implications – The findings highlight the need for more interdisciplinary and globally collaborative research in this domain. Future studies should bridge Islamic theological principles with inclusive pedagogical frameworks and expand beyond English-language and Scopus-indexed publications to achieve a more holistic understanding of inclusive Islamic education.